2014
DOI: 10.1186/ar4498
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and risk of rheumatoid arthritis: a dose-response meta-analysis

Abstract: IntroductionAlthough previous studies found that cigarette smoking is associated with risk of rheumatoid arthritis (RA), the dose-response relationship remains unclear. This meta-analysis quantitatively summarizes accumulated evidence regarding the association of lifelong exposure to cigarette smoking assessed as pack-years with the risk of RA.MethodsRelevant studies were identified by a search of MEDLINE and EMBASE from 1966 to October 2013, with no restrictions. Reference lists from retrieved articles were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
164
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(174 citation statements)
references
References 26 publications
3
164
2
5
Order By: Relevance
“…The association of smoking with development and severity of RA was documented almost 30 years ago [10] and confirmed in many subsequent studies [11][12][13][14][15][16][17][18][19][20][21]. A recent dose-response meta-analysis (encompassing 4,552 RA patients) reported relative risks of 1.26 and 1.96 for the associations of RA with smoking histories of 1-10 and >20 pack years respectively [19].…”
Section: Smoking and Ramentioning
confidence: 79%
See 1 more Smart Citation
“…The association of smoking with development and severity of RA was documented almost 30 years ago [10] and confirmed in many subsequent studies [11][12][13][14][15][16][17][18][19][20][21]. A recent dose-response meta-analysis (encompassing 4,552 RA patients) reported relative risks of 1.26 and 1.96 for the associations of RA with smoking histories of 1-10 and >20 pack years respectively [19].…”
Section: Smoking and Ramentioning
confidence: 79%
“…A recent dose-response meta-analysis (encompassing 4,552 RA patients) reported relative risks of 1.26 and 1.96 for the associations of RA with smoking histories of 1-10 and >20 pack years respectively [19]. In addition, others have reported that RAaffected male, current smokers were less likely to experience remission than their 4 never-or former-smoking counterparts, an association that was not detected in females [22].…”
Section: Smoking and Ramentioning
confidence: 99%
“…Smoking is a known risk factor for the development of rheumatoid arthritis (RA) 1. The prevalence of smoking is, therefore, higher in patients with RA than in the general population 2.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is recognized as an important risk factor for RA development and is associated with increased risk of comorbidities that are leading causes of death in RA, including cardiovascular and respiratory diseases (5)(6)(7)(8)(9)(10). Smoking cessation at any time after RA diagnosis was associated with decreased mortality risk in a recent large study in the UK (11).…”
Section: Introductionmentioning
confidence: 98%